(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2013)
This paper considers the phenomenon of ressentiment. It discusses ressentiment as the atmosphere of our culture and considers how it may shape our values. It also considers how ressentiment may be on the rise, due to an increasingly voracious culture of entitlement and decreasing tolerance of suffering.